The Steampunk Adventurer's Guide : Contraptions, Creations, and Curiosities Anyone Can Make - Willeford, Thomas (McGraw-Hill/TAB Electronics, 2013)
Fascinatingly Fun, Family-Friendly Steampunk Projects "Here's a Steampunk tale with an invitation to build Steampunk props. An interactive notion; an imaginative adventure; and a way to further stimulate your own imagination."--The Foreword by David Silverman, director and producer of The Simpsons Movie and codirector of Monsters, Inc. Steampunk stalwart Thomas Willeford cordially invites you on an adventure--one in which you get to build ingenious devices of your own! Lavishly illustrated by award-winning cartoonist Phil Foglio, The Steampunk Adventurer's Guide: Contraptions, Creations, and Curiosities Anyone Can Make presents 10 intriguing projects ideal for makers of all ages and skill levels, woven into an epic tale of mystery and pursuit. Follow the exploits of Isaac and Amelia, a brother and sister who must devise a series of beguiling gizmos to rescue their uncle from a skyship that's been commandeered by a nefarious villain and his rogue automatons. Each chapter contains an installment of this captivating story along with the step-by-step instructions and list of tools and materials you'll need to create the featured gadgets. Discover how to forge these imaginative contraptions: Decoder armguard Signaling periscope Goggles Grappling hook launcher Airship harness Glider wings Rivet gun Power armor Magnetic amplification gauntlet Rocket pack.